The governmental assistance to Korean NGOs. - Toiglova., A. B. (Journal of Oriental Studies, 2016)
In response to the growing role of civil society and NGOs, the Korean government has paid serious attention to the voices and activities of NGOs. There are both pros and cons to relations between government and NGOs, but government-NGO relations are gradually being accepted as inevitable. Along such a trend, this paper will review governmental assistance to Korean NGOs.